THE SPEECH ACT IN VERBAL COMMUNICATION OF A SCHIZOPHRENIC CHARACTER IN A BEAUTIFUL MIND MOVIE A CLINICAL PRAGMATIC ANALYSIS - Aris Hidayatulloh; Evi Murti Wardhani; Alif Rahmadhani (Proceeding of International Conference on Science, Health, And Technology, 2022)
Speech act is the study of the implied meaning uttered by the speaker to hearer. The study of speech act includes the locutionary act, illocutionary act, and perlocutionary act which become the basis when someone utters their utterance. Beside the three basic components, the involvement of cooperative principle is needed in communication. In other side, people with schizophrenia have some differences when they communicate. The perception of them is destructed by deletions and it will create misperception in communication. The phenomenon of speech act of schizophrenic becomes the study of this research. This research is discussed the representative speech act and the quality maxim of schizophrenic communication. The problem statements in this research are what kind of representative speech act is uttered and how the quality maxim takes role in schizophrenic. This research uses words, phrases, and sentences of representative utterances of John Nash in the film entitled A Beautiful Mind as the data mean while the movie, A Beautiful Mind, becomes the source of the data. The data are the utterances or sentences. The data will be obtained from the main character John Nash and focused on representative speech act and the quality maxims in Nash’s conversation. Each utterance chosen by the researcher will be the datum of this research. The movie, A Beautiful Mind, takes role as the source of the data.From the analysis, the types of the representative speech act uttered by John Nash in A Beautiful Mind movie are: claiming: 2 data, admitting: 1 datum, informing: 1 datum, denying: 1 datum, reporting: 1 datum, assuring: 1 datum, and concluding: 1 datum. The result shows that the most dominant data is claiming. The reason why it becomes the most dominant category is that the character tend to give claim to the people around him to make sure he is still be able to differ the reality or delusion.